Formally engaging the private sector for fecal sludge management services: experiences from six African cities - Will Tillett; Goufrane Mansour (2018)
In 2013, the Bill and Melinda Gates Foundation (BMGF), together with the UK Department for International Development launched the Partnership Cities Project, which aimed to support city authorities in developing onsite sanitation services and demonstrate approaches to formalize and regulate private sector participation (PSP) in service delivery. In Sub-Saharan Africa, six grantees were supported to develop urban onsite sanitation service across the sanitation value chain. This paper presents the findings from a review of these projects. Lessons indicate that projects succeeded in improving onsite sanitation services at city-level through the development of much needed infrastructure, and formalizing PSP through PPP contracts and licensing. Projects also demonstrated approaches to regulating onsite services, including through call centers and strengthening legal frameworks. As a result, city authorities have become better equipped for addressing the challenges of urban sanitation services. However further research is needed to establish services’ sustainability and pro-poor outcomes.